Image Processing Analysis of Prevention for Mold Growth on Bread using Negative Ion Technology - Liew, Chun Keat; M. Z., Ibrahim; Mohd Hisyam, Mohd Ariff (UTeM, 2017)
Recently, molds on bread can cause Diarrhae, allergic reactions and respiratory problems. The molds like Aspergillus, Fusarium and Penicillium can produce "Mycotoxins" which a poisonous substances that can damage the health qualities. Thus, the prevention of mold growth on bread by using negative ion technology is the best alternatives to break the disease. The effect of negative ions can be classified to spatial distribution of charge particles, sheath structure and collaboration of ozone and negative air ions to prevent microorganism. In this paper, image processing has been used to analyse the image obtained from the bread after a week. Two experiments have been compared to keep track the effect of negative ions on prevention of mold growth on bread which are bread placed in boxes with direct current (DC) fan or without it. In set one, the mold percentages of bread that exposed to negative ions is 3.47% while the bread that does not exposed to negative ions is 14.60%. Moreover for the set two, the mold percentages of bread that exposed to negative ions is 1.18% while the bread that does not exposed to negative ions is 14.18%. Set two have a lower percentage of mold as compare to set one due to the air ventilation of the experiment set up. Each of experiment has been analysed using color filtering processing and the result shows that negative ions was successfully in the prevention of mold growth on bread.